Where my heart is turning ever : Civil War stories and constitutional reform, 1861-1876 - Diffley, Kathleen Elizabeth, 1950- (University of Georgia Press, 1992)
"During the Civil War and Reconstruction, popular magazines throughout the country published hundreds of short narratives that confronted or evaded the meaning of the Union's great crisis. Yet despite their importance as a measure of the era's cultural temper, these stories have remain largely unexamined in studies of Civil War literature. Where My Heart is Turning Ever is the first volume in a projected trilogy that seeks to recover the significance of this forgotten body of writing. Unearthing more than three hundred stories from sixteen magazines in the South and West as well as the culturally dominant Northeast, Kathleen Diffley examines the effort of popular writers and publications to contain the disruption caused by the war and its aftermath. That effort, she shows, proved especially precarious when writers took up matters of race, political section, and gender. In this volume, Diffley identifies three distinct genres among the stories she investigates: "Old Homestead," which embodies themes of domestic order, collapse, and restoration; "Romance," which represents tensions between the sexes as the result of difficulties imposed by the war and Reconstruction; and "Adventure," which subverts domestic ideals by uprooting characters and situating them outside the home. As she discusses these genres, Diffley relates their messages to the post-bellum congressional debates over constitutional amendments abolishing slavery, guaranteeing federal authority over state jurisdictions, and extending voting rights to black men. She hows how the rhetoric that emerged both in Congress and in popular magazines promoted a new concept of national citizenship, one that transformed ties to kin into ties to country. In addition to discussing the broad spectrum of stories that fall within the three genres she identifies, Diffley includes full text of representative stories by Mark Twain, John W. De Forest, and Rebecca Harding Davis. She then analyzes each story, linking its author's career with the wider cultural and formal patterns that the story reveals. In the subsequent volumes of the trilogy, Diffley will provide a taxonomy of the stories she has uncovered and will examine them in light of reader-response theory. The completed project promises an unprecedented analysis of the ways in which short popular narratives helped readers of that troubled era make sense of the Civil War."--Publisher's description